Problem Based Business Development Through System Digitalization In Optimizing The Creative Economy - Yuliana Justi, Helmina; Mallongi, Syahrir; Abdullah, Wahyuddin; Jamaluddin (LAA MAISYIR: Jurnal Ekonomi Islam, 2023)
This research aims to analyze the concept of maslahah in franchise businesses through a digitalization system. This type of research is qualitative research using a phenomenological approach. A phenomenological approach is used to see the extent to which franchise businesses carry out business activities in Palopo City. Therefore, this research is considered important in describing the concept of maslahah in franchise business practices through a digitalization system. The data collection method involves three stages, namely observation, interviews and documentation. Data analysis, namely data reduction, data presentation, and drawing conclusions. The research results show that franchise business practices in the city of Palopo are businesses that comply with Islamic law. The form of a franchise business cooperation agreement is like a syirkah, namely leasing. The concept of maslahah includes: maintaining religion, maintaining the soul in the form of ethics between people without any differences, maintaining reason, namely the way of thinking in dealing with problems, maintaining offspring in the form of maintaining life as a form of maintenance and maintaining assets which is realized that in assets there are other people's rights. Furthermore, the concept of maslahah through digitalization, optimizing the creative economy is a form of renewal that must be carried out to support business careers in the future while remaining guided by justice and honesty for the sustainability of the creative economy industry.